ChemInform Abstract: Sequential Friedel—Crafts‐Type α‐Amidoalkylation/Intramolecular Hydroarylation: Distinct Advantage of Combined Tf2NH/Cationic LAu(I) as a Consecutive or Binary Bicatalytic System. Issue 36 (September 2015) - Boiaryna, Liliana; Azizi, Mohamed Salah; El Bouakher, Abderrahman; Picard, Baptiste; Taillier, Catherine; Othman, Mohamed; Trabelsi‐Ayadi, Malika; Dalla, Vincent
Abstract The process gives polycyclic heterocycles generally as separable mixtures of 6‐exo‐dig and 7‐endo‐dig cyclization products.